2015
DOI: 10.1371/journal.pone.0139493
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Date Palm Pollen for Testicular Dysfunction Induced by Thyroid Disorders in Male Rats

Abstract: Hyper- or hypothyroidism can impair testicular function leading to infertility. The present study was designed to examine the protective effect of date palm pollen (DPP) extract on thyroid disorder-induced testicular dysfunction. Rats were divided into six groups. Group I was normal control. Group II received oral DPP extract (150 mg kg-1), group III (hyperthyroid group) received intraperitoneal injection of L-thyroxine (L-T4, 300μg kg-1; i.p.), group IV received L-T4 plus DPP extract, group V (hypothyroid gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 55 publications
(67 reference statements)
4
28
0
Order By: Relevance
“…Krassas, Papadopoulou, Tziomalos, Zeginiadou, and Pontikides () and Sarma, Saikia, and Das () showed in the clinical prospective studies that hypothyroidism is associated with sperm alteration in adult men. Several studies conducted on animal models revealed a fall in circulating testosterone, follicle‐stimulating hormone (FSH) and luteinising hormone (LH) and altered spermatogenesis in hypothyroid subjects (El‐Kashlan, Nooh, Hassan, & Rizk, ; Hoda & Abdelaziz, ; Tahmaz et al, ). Decrease in sperm cell count and sperm motility, and increase in dead and abnormal sperm count were also reported (El‐Kashlan et al, ; Hoda & Abdelaziz, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krassas, Papadopoulou, Tziomalos, Zeginiadou, and Pontikides () and Sarma, Saikia, and Das () showed in the clinical prospective studies that hypothyroidism is associated with sperm alteration in adult men. Several studies conducted on animal models revealed a fall in circulating testosterone, follicle‐stimulating hormone (FSH) and luteinising hormone (LH) and altered spermatogenesis in hypothyroid subjects (El‐Kashlan, Nooh, Hassan, & Rizk, ; Hoda & Abdelaziz, ; Tahmaz et al, ). Decrease in sperm cell count and sperm motility, and increase in dead and abnormal sperm count were also reported (El‐Kashlan et al, ; Hoda & Abdelaziz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conducted on animal models revealed a fall in circulating testosterone, follicle‐stimulating hormone (FSH) and luteinising hormone (LH) and altered spermatogenesis in hypothyroid subjects (El‐Kashlan, Nooh, Hassan, & Rizk, ; Hoda & Abdelaziz, ; Tahmaz et al, ). Decrease in sperm cell count and sperm motility, and increase in dead and abnormal sperm count were also reported (El‐Kashlan et al, ; Hoda & Abdelaziz, ). Jiang, Umezu, and Sato () observed a significantly high frequency of epididymal spermatozoa with cytoplasmic droplets and alteration in fertilization potential in vivo or in vitro in hypothyroid state.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have concluded that dietary supplementation could improve spermatogenesis, increase sperm counts, motility, and increase the concentration of testosterone, FSH and LH (Salman et al, 2014;Baharara et al, 2015;El-Kashlan et al, 2015;Rasekh et al, 2015). Also, DPPG is a rich source of natural antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Also, DPPG is a rich source of natural antioxidants. El-Kashlan et al (2015) observed that DPPG extract possessed a powerful free radical scavenging capacity. Hassan (2011) and Bishr & Desoukey (2012) attributed the powerful antioxidant capacity of pollen grain to its high content of phenolic, carotenoid, flavonoid compounds, and considerable amount of vitamins A, E and C. Moreover, pollens have antibacterial, antifungal and antiviral activity (Abedi et al, 2012;Mallhi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The early Egyptians and ancient Chinese used pollen as a rejuvenating medicinal agent. It has been called a "fountain of youth" 4 .Regular consumption of DPP is beneficial in nephropathy, rheumatism,gastropathy, sexual debilityand DPP extract have potential protective effects on testicular dysfunction induced by altered thyroid hormones 5,6 . In addition DPP grains have antioxidant and hypolipidemic effect in which exhibited significant reduction for serum cholesterol and low density lipoptoein-cholesterol(LDL-C), triglycerides and improve the level of high density lipoprotein-cholesterol( HDL-C), also the isolated flavonoids from DPP have anti atherosclerotic effects in high dose 7 .…”
Section: Introductionmentioning
confidence: 99%